Sodium pumps, ouabain and aldosterone in the brain: A neuromodulatory pathway underlying salt-sensitive hypertension and heart failure. (March 2020) - Leenen, Frans H.H.; Wang, Hong-Wei; Hamlyn, John M.
Graphical abstract: Highlights: Excess salt and/or angiotensin II stimulate a neuroendocrine pathway in the brain and raise blood pressure. The pathway involves three hormone-receptor pairs that work in a sequential manner. The pairs are: aldosterone and mineralocorticoid receptors, endogenous ouabain/α2 sodium pumps, and angiotensin II and its type 1 receptors. Activation of the pathway amplifies angiotensin II-evoked signaling in the paraventricular nucleus and increases sympathetic activity. In summary, pathway hormones regulate ion transport mechanisms in the brain that underlie hypertension and adverse outcomes in heart failure. Abstract: Accumulating evidence obtained over the last three decades has revealed a neuroendocrine system in the brain that mediates long term increases in blood pressure. The system involves distinct ion transport pathways including the alpha-2 isoform of the Na, K pump and epithelial sodium channels, as well as critical hormone elements such as angiotensin II, aldosterone, mineralocorticoid receptors and endogenous ouabain. Activation of this system either by circulating or central sodium ions and/or angiotensin II leads to a cascading sequence of events that begins in the hypothalamus and involves the participation of several brain nuclei including the subfornical organ, supraoptic and paraventricular nuclei and the rostral ventral medulla. Key events include heightened aldosterone synthesis and mineralocorticoid receptor activation, upregulation of epithelial sodium channels, augmented synthesis and secretion of endogenous ouabain from hypothalamic magnocellular neurons, and sustained increases in sympathetic outflow. The latter step depends upon increased production of angiotensin II and the primary amplification of angiotensin II type I receptor signaling from the paraventricular nucleus to the rostral ventral lateral medulla. The transmission of sympathetic traffic is secondarily amplified in the periphery by increased short- and long-term potentiation in sympathetic ganglia and by sustained actions of endogenous ouabain in the vascular wall that augment expression of sodium calcium exchange, increase cytosolic Ca 2+ and heighten myogenic tone and contractility. Upregulation of this multi-amplifier system participates in forms of hypertension where salt, angiotensin and/or aldosterone are elevated and contributes to adverse outcomes in heart failure.